2005
DOI: 10.1111/j.1478-3231.2005.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the ablated area by the spread of microbubbles during radiofrequency ablation of hepatocellular carcinoma

Abstract: The observation of microbubbles during RFA can predict the ablated area and might be useful to prevent the unfavorable ablation of adjacent organs and vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Some reports suggest that automated pulsing at a higher RF current with internally cooled electrodes has further increased coagulation necrosis compared to continuous RF application in liver tissues [8, 17]. On the other hand, a modified pulsed algorithm was used recently which depends on a gradual stepwise increase of the RF current at a fixed duration by manually adjusting the power setting until rapid tissue impedance is reached followed by a period of low-energy deposition [3, 14, 15]. Achievement of maximum tissue impedance is related to the heat produced by the RF current and the subsequent coagulation, which represents complete necrosis over the thermal area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports suggest that automated pulsing at a higher RF current with internally cooled electrodes has further increased coagulation necrosis compared to continuous RF application in liver tissues [8, 17]. On the other hand, a modified pulsed algorithm was used recently which depends on a gradual stepwise increase of the RF current at a fixed duration by manually adjusting the power setting until rapid tissue impedance is reached followed by a period of low-energy deposition [3, 14, 15]. Achievement of maximum tissue impedance is related to the heat produced by the RF current and the subsequent coagulation, which represents complete necrosis over the thermal area.…”
Section: Discussionmentioning
confidence: 99%
“…For the manual algorithm [3, 14, 15], the power output was initially set at 60 W then increased manually at 20 W per minute to reach up to 120 W. Power is maintained at this level until rapid tissue impedance is achieved. The power is then manually turned off for 15 s. Afterwards, the power output is restarted with a 20-watt reduction from the previous highest reading and gradually increased by 20 W/min until rapid tissue impedance is observed.…”
Section: Methodsmentioning
confidence: 99%
“…The spread of the hyperechoic area by ablation was reported to be useful to estimate the boundaries of the ablated area (22,23), while Nouso et al reported that the size of the area of hyper-echogenicity at 5 min after ablation and that of the defect observed by CEUS 3-5 days after RFA were closely correlated (24). These findings led us to use hyper-echoic microbubbles at 5 min after ablation for determining the area of necrosis.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…After the ablation, we evaluated whether the overlaid tumor was completely encompassed with the spreading hyperechoic bubbling area [12,13]. If an overlaid tumor was protruding from the bubbling area, additional ablation was performed until it was completely within the bubbling area.…”
Section: Methodsmentioning
confidence: 99%